STUDYING FETAURES OF ORAL MICROFLORA AND SENSITIVITY OF FUNGI CANDIDA AGAINST MODERN ANTI-FUNGAL MEDICINES AT PATIENTS WITH ORAL CANDIDIASIS AT THE BACKGROUND OF DIABETES MELLITUS TYPE 1 - Nikolishin, A.K.; Stupak, О.P.; Stupak, P.P. (World of Medicine and Biology, 2010)
In these was investigated oral microflora and performed sensitivity estimation of fungi Candida against modern anti-fungal medicines, widely used in dental practice at patients with oral candidiasis at the background of diabetes mellitus type 1.
Keywords: oral candidiasis; diabetes mellitus